Productivity Growth and its Influence on the Dollar/Euro Real Exchange Rate (Global Journal of Management and Business Research, 2012)
This paper examines the evidence for a productivity based model of the dollar/euro real exchange rate for the period 1985-2007 period. Cointegrating relationships between the real exchange rate and productivity, real price of oil and government spending are estimated using the Johansen and Stock-Watson procedures. The findings show that for each percentage point in the US-Euro area productivity differential there is a three percentage point change in the real dollar/euro valuation. These findings are robust to the estimation methodology, the variables included in the regression, and the sample period.